To solve the system of equations using elimination, we'll manipulate the equations to eliminate one of the variables. The given equations are:
-
\(4x - 6y = -48\)
-
\(-2x + 4y = 30\)
First, we can multiply the second equation by 2 to make the coefficients of \(x\) in both equations match:
Multiplying the second equation by 2 gives:
\[ -4x + 8y = 60 \]
Now we rewrite the system of equations:
-
\(4x - 6y = -48\)
-
\(-4x + 8y = 60\)
Next, we add the two equations together to eliminate \(x\):
\[ (4x - 6y) + (-4x + 8y) = -48 + 60 \]
This simplifies to:
\[ 0x + 2y = 12 \]
This means:
\[ 2y = 12 \]
Dividing both sides by 2 gives us:
\[ y = 6 \]
Now that we have \(y\), we can substitute this value back into one of the original equations to find \(x\). We'll use the first equation:
\[ 4x - 6(6) = -48 \]
This simplifies to:
\[ 4x - 36 = -48 \]
Adding 36 to both sides:
\[ 4x = -48 + 36 \] \[ 4x = -12 \]
Dividing both sides by 4 gives:
\[ x = -3 \]
Thus, the solution to the system of equations is:
\((-3, 6)\)
So the correct response is:
(−3, 6)